If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 3x + -25 Reorder the terms: 6 = -25 + 3x Solving 6 = -25 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6 + -3x = -25 + 3x + -3x Combine like terms: 3x + -3x = 0 6 + -3x = -25 + 0 6 + -3x = -25 Add '-6' to each side of the equation. 6 + -6 + -3x = -25 + -6 Combine like terms: 6 + -6 = 0 0 + -3x = -25 + -6 -3x = -25 + -6 Combine like terms: -25 + -6 = -31 -3x = -31 Divide each side by '-3'. x = 10.33333333 Simplifying x = 10.33333333
| 7234.56=3.14r^2 | | 4t^4+18t^3-10t^2=0 | | x-5.5=-6.3 | | 5x-2(-7x+11)=16 | | (2/5n)7 | | j+(0.5*j-8)=100 | | x^2+3x-50=0 | | 7-7x-2=-22+3x-13 | | 7/5=10.5b | | 10b^2-26b+12=0 | | X/3-5=-4 | | 8-y=15 | | 5x=-5y+65 | | 7-9x-2=-46+7x-13 | | X^2+2x+.4=.9x^2+x | | X=-5y+25 | | (5x+6)(5x-5)= | | -9x-5=9-2x | | -16/3/2/3 | | 2m/n-5m/3n | | 3y-2=6-y | | .5(6x+4)=4x-9 | | -51/3x/2/3 | | 15(b+6)-9b= | | 3x^4+19x^3+6x^2=0 | | 2p^2+21p+40=0 | | -56=a^2+18a | | 3/4(4x8-8)=-10 | | -6=2a-3 | | 7-8x-3=-65+6x-15 | | 4d+5d=54 | | 11/3x22/5 |